2020
DOI: 10.1007/s42757-020-0061-7
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of fiber transport in human respiratory airways—A review

Abstract: Investigations on the respiratory transport and deposition of airborne asbestos, man-made vitreous fibers (MMVFs), and carbon nanofiber/carbon nanotubes have been actively conducted in the past few decades. The elongated particles' distinctive needle-like geometry has been identified as the main cause of extreme carcinogenicity when compared to inhaled spherical particles. Consequently, uncovering the intrinsic relationship between the particle's unique elongated shape and its transport characteristics in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 92 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…The results showed that nasopharynx obstruction can induce significantly biased flow distribution in the central nasal passage even if the obstruction site is downstream of the nasal airway. Some review papers offered several works; for example, Tian and Ahmadi [90] studied the current state of computational modeling of micron and nano-elongated particle dynamics and their application to fiber transport and deposition in human respiratory airways; the most versatile and practical approach was the Eulerian-Lagrangian. Ma et al [91] analyzed the parameters that affect the thermal performance of latent heat thermal energy storage systems (LHTES), including the inlet temperature of the heat transfer fluid, heat transfer rate, properties of the phase-change materials (PCMs), phase-change temperature, geometric parameters, and water tube layout, among others.…”
Section: Software For Selecting Desiccant Wheelsmentioning
confidence: 99%
“…The results showed that nasopharynx obstruction can induce significantly biased flow distribution in the central nasal passage even if the obstruction site is downstream of the nasal airway. Some review papers offered several works; for example, Tian and Ahmadi [90] studied the current state of computational modeling of micron and nano-elongated particle dynamics and their application to fiber transport and deposition in human respiratory airways; the most versatile and practical approach was the Eulerian-Lagrangian. Ma et al [91] analyzed the parameters that affect the thermal performance of latent heat thermal energy storage systems (LHTES), including the inlet temperature of the heat transfer fluid, heat transfer rate, properties of the phase-change materials (PCMs), phase-change temperature, geometric parameters, and water tube layout, among others.…”
Section: Software For Selecting Desiccant Wheelsmentioning
confidence: 99%
“…Nowadays, ozone pollution is becoming increasingly serious worldwide, threatening environmental safety and human health. , Outdoor ozone pollution mainly originates from exhaust of industrial fields like deodorization, wastewater treatment, bleaching, and sterilization, while indoor ozone pollution is caused by common electronic equipment such as copiers, air purifiers, dish washers, and air conditioners . Due to the resonance stability, the half-time of ozone is as long as 160 h at 25 °C, , which necessitates a safe, effective, and economical method to remove ozone pollution .…”
Section: Introductionmentioning
confidence: 99%